Power density spectra morphologies of seismically unresolved red-giant asteroseismic binaries - Choi, Jeong Yun; Espinoza-Rojas, Francisca; Coppée, Quentin; Hekker, Saskia (Astronomy and astrophysics, 2025)
Methods. We created 5000 artiﬁcial asteroseismic binary (AAB) systems by combining the KASOC light curves of red giants with oscillations at similar frequency ranges. To quantify the complexity of the oscillation patterns, we used the maximum signal-to-noise ratio of the background-normalized PDS and Shannon entropy. Additionally, we identiﬁed the radial and quadrupole mode pairs for the individual binary component and determined their impact on the PDS morphologies of AABs. - Results. Our results reveal that the majority of AABs (∼47%) consist of the two red-clump stars. The PDSs of AABs generally exhibit increased Shannon entropy and decreased oscillation power compared to individual components. We focused on the ∼8% of AABs whose stellar components have a similar brightness and classiﬁed them into four distinct morphologies: (i) single star-like PDSs, whereby oscillations from one component dominate, (ii) aligned, whereby the dominant oscillations in the stars that form the AAB appear at similar frequencies, (iii) partially aligned, whereby some oscillation modes of component stars are aligned while others are not, and (iv) PDSs containing complex structures with unclear mode patterns caused by the misalignment of the mode frequencies of both components. - Conclusions. We found that most AABs with detectable oscillations from both components show complex oscillation patterns. Therefore, unresolved asteroseismic binaries with a low oscillation power and complex oscillation patterns as characterized by high Shannon entropy oﬀer a potential explanation to understand the observed stars with complex PDSs.
Gesehen am 17.11.2025